Development through Literacy : A Study of Fishing Community in Andhra Pradesh - Surapa Raju, S. (Journal of Rural Development, 2010)
The study looks into the participation and usefulness of the Akshara Bharathi (adult literacy) Programme among the people belonging to fishing community in the State of Andhra Pradesh (India). Out of the three literacy components-reading, writing and simple arithmetic more achievement was observed in reading skills than the other two. Fisherwomen actively participated and the level of achievement was more than the fishermen due to their consciousness to learn the 3 "R"s, which are needed, in their fish marketing activity. The literacy skills learned from the Akshara Bharathi have a positive impact on people belonging to fishing community on socioeconomic development of the family in terms of increase in the family income, children's education, and health situation and family welfare. There is a need to cover all the leftover illiterate persons particularly males by propagating the usefulness of the programme through various mass media channels. Proper supervision is very much essential to achieve better results for the existing programmes. The government has to initiate the establishment of "Corpus Fund" exclusively for attainment of total literacy in the fishing villages by deducting some percentage of foreign exchange earned from fish exports.